Progressive taxes and the labour market: Is the trade-off between equality and efficiency inevitable? - Knut Røed; Steinar Strøm (University of Oslo, Department of Economics, 1999)
Does an income tax harm economic efficiency more the more progressive it is? Public economics provides a strong case for a definite `yes'. But at least three forces may pull in the other direction. First, low-wage workers may on average have more elastic labour supply schedules than high-wage workers, in which case progressive taxes contribute to a more efficient allocation of the total tax burden. Second, in noncompetitive labour markets, progressive taxes typically encourage wage moderation, and hence reduce the equilibrium level of unemployment. And third, if wage setters have egalitarian objectives, progressive taxes may reduce the need for redistribution in pre-tax wages, and hence increase the demand for low-skilled workers. This paper surveys the theoretical, as well as the empirical literature about labour supply, taxes and wage setting. We conclude that in a second best world, the trade-off between equality and efficiency is not always inevitable.
Keywords: H24; J30; J58; 330; Tax progressivity; dead-weight loss; redistribution; Steuerprogression; Einkommensteuer; Allokationseffizienz; Einkommensumverteilung; Arbeitsmarkt; Theorie